Case Report: Two highly unusual adrenal tumors presenting with hypertension: a giant cystic pheochromocytoma with an ipsilateral large renal parapelvic cyst and a giant adrenal myelolipoma - Konus, Ali Hakan; Ugur, Kader; Aygen, Erhan; Tektas, Cihat; Durumlu, Fatih; Calik, Muhammet (Frontiers Media Sa, 2025)
Background Giant cystic pheochromocytoma and giant adrenal myelolipoma are two highly uncommon masses. There are difficulties in diagnosis and management of both types of giant (>20 cm) adrenal tumors. Case 1 A 56-year-old male patient applied with complaints of headache and high blood pressure. A mass was palpated in the left upper quadrant. The average 24-hour ambulatory blood pressure was 146/93 mm Hg. Computed tomography revealed a huge left adrenal cystic mass measuring 22 x 17 cm. A large left renal parapelvic cyst measuring 6 x 5.5 cm was also observed. Urine metanephrine and normetanephrine values were high. The patient was diagnosed with pheochromocytoma. It was decided to remove the adrenal cystic mass and renal parapelvic cyst with open surgery. Severe hypotension occurred during the intraoperative and early postoperative periods, and severe orthostatic dizziness occurred during the in-hospital stay and two months of outpatient follow-up. The patient's urine metanephrine and normetanephrine levels returned to normal. The average 24 h ambulatory blood pressure was 122/69 at six months. Case 2 A 53-year-old male patient was admitted with complaints of high blood pressure, accompanied by mild headache and dizziness that had been ongoing for several months. A mass was palpated in the right upper quadrant. The average 24 h ambulatory blood pressure was 151/91 mm Hg. Abdominal computed tomography revealed a 24 x 16 x 22 cm solid mass with diffuse fat density originating from the right adrenal gland. Laboratory studies and endocrine investigations were normal. With the diagnosis of adrenal myelolipoma, a mass weighing 4,229 g was surgically removed. The patient was normotensive without medical treatment during the two-year follow-up after the operation. Conclusion To our knowledge, our case of giant cystic pheochromocytoma accompanied by ipsilateral large renal parapelvic cyst, which is the first in the literature, reports the management of severe hypotension in the perioperative period and severe orthostatic dizziness in the two-month follow-up. Non-functional adrenal myelolipomas can cause hypertension with mass effect. Our second case is one of the largest adrenal myelolipomas in literature. Although surgical removal of giant masses is difficult, successful surgeries have resulted in resolution of hypertension in our cases at mid-term follow-up.
Keywords: giant cystic pheochromocytoma; giant adrenal myelolipoma; adrenal tumor; large renal parapelvic cyst; hypertension; orthostatic dizziness